Multiproxy analysis of omnivore and herbivore coprolites: Inferences on Mid-Holocene dietary habits in Argentine Patagonia. (10th November 2021) - Velázquez, Nadia Jimena; Martínez Tosto, Ana Cecilia; Benvenuto, María Laura; Fernández, Natalia; Civalero, María Teresa; Burry, Lidia Susana
Abstract: Learning about past biological interactions is possible thanks to the study of trace fossils, such as coprolites found in archaeological sites. The multiproxy analysis of coprolites may provide evidence of direct and indirect consumption of diet items and thus reconstructing the ecological dynamics of past ecosystems. In this study, we performed a comparative analysis of the content of plant fragments, pollen and silica phytoliths in coprolites found in the archaeological site Cerro Casa de Piedra 5 (47°57′S; 72°05′W), located in the Perito Moreno National Park, Santa Cruz, Argentina, in an archaeological layer dated to 6540 ± 110 years 14 C BP (7402 cal years BP), with the aim to recognize dietary habits in those times. According to their morphological features and content, the coprolites were assigned to omnivores (humans/canids) and herbivores (camelids). The multiproxy analysis of these coprolites allowed us to reach a higher taxonomic resolution in the identification of some plant items in the diet, to make inferences on the indirect consumption of vegetation through the consumption of stomachs and other viscera of camelids by omnivores, and to observe similarities and complementarities in terms of the presence and abundance of taxa. The limitations and potentialities of multiproxy analysis to infer past dietary habits are discussed. The information obtained provides greater knowledge about the predator-prey interactions of the Middle Holocene in south-western Patagonia.